(untitled) (Physical Education, Health and Social Sciences, 2025)
Surgical site infections (SSIs) remain a major cause of postoperative complications, leading to increased morbidity, prolonged hospital stays, and higher healthcare costs. This study examines multiple risk factors contributing to SSIs, including patient demographics, surgical history, postoperative care, infection indicators, healthcare provider practices, antibiotic resistance patterns, environmental influences, surgical team compliance, and nutritional status. A total of 138 patients undergoing various surgical procedures were analyzed. Data were collected on demographic characteristics, type of surgery, duration of hospital stay, wound care practices, presence of infections, antibiotic use, and compliance with infection control measures. Microbiological analysis identified common bacterial pathogens and their antibiotic resistance patterns. Environmental conditions and healthcare provider adherence to infection prevention protocols were also assessed. Statistical analysis was performed to determine significant associations between these factors and SSI incidence. SSIs were confirmed in 23.2% of patients, with Staphylococcus aureus (34.4%), Escherichia coli (28.1%), and Pseudomonas aeruginosa (21.9%) being the most common pathogens. Methicillin-resistant S. aureus (MRSA) was identified in 41.2% of cases, while fluoroquinolone and carbapenem resistance were prevalent among E. coli and Klebsiella pneumoniae. Key risk factors for SSIs included emergency surgeries (34.8%), prolonged surgical duration (>2 hours, 23.9%), inadequate postoperative wound care, and poor nutritional status. Environmental conditions, including high patient density and inadequate ventilation, were also linked to higher SSI rates. Compliance with infection control protocols varied, with only 36.2% of suspected infection cases involving patient isolation. Malnourished patients had a significantly higher SSI incidence (28.6%) and longer recovery times compared to well-nourished individuals. The findings emphasize the need for a multifaceted approach to SSI prevention, incorporating strict infection control measures, antibiotic stewardship, environmental optimization, and perioperative nutritional support. Strengthening surgical team compliance, improving postoperative wound care, and addressing modifiable patient risk factors can significantly reduce SSIs and enhance patient outcomes. Future research should focus on long-term strategies to mitigate antimicrobial resistance and develop advanced infection prevention protocols.